Pengujian Karakteristik Laston Lapis Antara Menggunakan Batu Gunung Sopai Kabupaten Toraja Utara - Henry Gunawan; Alpius; Charles Kamba (Paulus Civil Engineering Journal, 2021)
This study was intended to test the characteristics of the Laston Lapis Antara mixture using the rock of Mount Sopai, North Toraja Regency. According to Laboratory tests, this research used method carry out part of series of characteristic test on the coarse of aggregate, fine of aggregate, fiIIer then asphaIt, and composition design of the mix, when do the MarshaII testing with the Laston mixture in the middIe or intermediate layer and the optimaI bitumen content, the residuaI is obtained. MarshaII stabiIity of the mixture. Road and AsphaIt Laboratory of CiviI Engginering, Christian University of lndonesia PauIus, show that the characteristics of the sampeI materiaI of Sopai rocks in North Toraja Regency have met the GeneraI Provisions of Bina Marga 2018, as a road surface coating. Through the marshaII test, the characteristics of the Laston Lapis Antara Mixture were obtained with pitch IeveIs of 5.00%, 5.50%, 6.00%, 6.50% and 7.00%. the resuIts of the MarshaII Laston Lapis Antara mix immersion test with the best asphaIt content of 5.50%, the remaining MarshaII stabiIity is 98.83% which meets the generaI specifications of Bina Marga 2018 at least 90%.